(untitled) (British Journal of Global Ecology and Sustainable Development, 2025)
This article investigates the long-term urogenital system disorders in patients who have recovered from COVID-19. The study focuses on kidney function, urinary tract, and male and female reproductive health. Clinical observations revealed significant post-COVID changes in nephrological and reproductive functions. The article analyzes the pathophysiological mechanisms, laboratory and instrumental diagnostics, and promising therapeutic approaches.